Training Future Actors in the Food System: a new collaborative cross-institutional, interdisciplinary training programme for students. (2017) - Reed, Kelly; Collier, Rosemary; White, Rebecca; Wells, Rebecca; Ingram, John; Borelli, Rosina; Haesler, Barbara; Caraher, Martin; Lang, Tim; Arnall, Alex; Gonzalez, Raquel Ajates; Pope, Harley; et al.
No abstract available